Multi-dimensional earthquake vulnerability assessment of residential neighborhoods of Mymensingh City, Bangladesh: A spatial multi-criteria analysis based approach - Md. Shaharier Alam; Shamim Mahabubul Haque (Journal of Urban Management, 2022)
The assessment of the vulnerability of a city to different natural hazards is the prerequisite to achieving sustainable urban resilience. The city of Mymensingh is located in the most earthquake vulnerable zone of Bangladesh and surrounded by multiple fault lines including the Madhupur Blind Fault, Dauki Fault, and Sylhet-Assam Fault lines. The city also achieved the title of the 8th divisional city in 2015, thereby opening the door to unrestrained future development. Therefore, it is of paramount importance to assess the earthquake vulnerabilities of Mymensingh city and this research is envisioned to evaluate this vulnerability by combining 23 parameters derived from four major dimensions-geological, socio-economic, structural and systematic dimensions. The MCDM techniques of Analytical Hierarchy Process and Weighted Linear Combination coupled with GIS-based spatial analysis were applied in this study to assess the residential neighborhood-level earthquake vulnerability. The findings show that out of the 241 residential neighborhoods of Mymensingh city, 51 are observed to be highly vulnerable, while 123 are exposed to medium vulnerability and 67 to low vulnerability. According to the analysis, the topmost factors that make Mymensingh City highly earthquake-vulnerable are the soil type, proximity to the fire station, elderly population levels, Peak Ground Acceleration, child population levels and distance to healthcare facilities. The simplistic, efficient, and reasonably accurate methodology and findings of this research are expected to be helpful for policymakers in low-income countries to prioritize special consideration areas, resource targeting, and deciding on appropriate planning and development control interventions for disaster management.
Keywords: 710; City planning and development; Earthquake vulnerability; GIS; Multi-criteria decision making